2016
DOI: 10.1007/s10803-016-2920-4
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Screen-Time Behavior, and Obesity Among 13-Year Olds in Ireland with and without Autism Spectrum Disorder

Abstract: The primary purposes of this study were to compare (a) physical activity participation, screen-time habits, obesity, and (b) reported reasons for lack of participation in sport, between a nationally representative sample of Irish children with and without autism spectrum disorder (ASD). Participation in moderate to vigorous activity, light activity, and sports was significantly lower among the group with ASD. On examination of screen time variables, no significant differences were seen between groups. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
84
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 98 publications
(97 citation statements)
references
References 42 publications
9
84
2
2
Order By: Relevance
“…The studies encompassed a total of 49,937,078 participants and 1,045,538 individuals with ASD. Ten studies were carried out in the United States 2427,29,30,3437 , two in Brazil 9,31 , one in Turkey 32 , one in Spain 33 , and one in China 28 . The sample sizes ranged from 40 33 to 986,352 30 individuals with ASD and from 19 9 to 48,598,466 30 controls.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies encompassed a total of 49,937,078 participants and 1,045,538 individuals with ASD. Ten studies were carried out in the United States 2427,29,30,3437 , two in Brazil 9,31 , one in Turkey 32 , one in Spain 33 , and one in China 28 . The sample sizes ranged from 40 33 to 986,352 30 individuals with ASD and from 19 9 to 48,598,466 30 controls.…”
Section: Resultsmentioning
confidence: 99%
“…For the method of ascertaining ASD, four studies used parental reports 26,29,30,36 , and the other studies based on their diagnoses on the Diagnostic and Statistical Manual (DSM-IV) 31,32,34 , DSM-V 9,28,32 , Social Communication Questionnaire (SCQ) 24 , International Classification of Diseases, 9th Revision (ICD-9) 25 , International Classification of Diseases, 9th Revision, Clinical Modification (ICD-9-CM) 27,35 , Autism Diagnostic Interview-Revised (ADI-R) 24,33,37 , Autism Diagnostic Observation Schedule (ADOS) 24,34 , and Autism Diagnostic Observation Schedule-Generic (ADOS-G) 33 . For the method of ascertaining BMI, three studies included parentally reported data 26,30,36 , ten studies objectively measured the data 9,24,2729,3134,37 , and two studies extracted the information from the participants’ medical records 25,35 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the presence of a chronic condition is associated with decreased physical activity and increased levels of sedentary behaviour due to barriers at all levels of the social‐ecological model . This has been documented for youth with a range of chronic conditions and disabilities . Finally, medications, commonly used for the management of chronic conditions, may contribute to weight gain …”
mentioning
confidence: 97%